'Seen but not heard'. Practitioners work with poverty and the organising out of disadvantaged children's voices and participation in the early years. Issue 2 (4th March 2017) - Simpson, Donald; Loughran, Sandra; Lumsden, Eunice; Mazzocco, Philip; Clark, Rory McDowall; Winterbottom, Christian
ABSTRACT: Living in poverty disadvantages young children reducing school readiness. 'Pedagogy of listening' can potentially support resilience remediating against poverty's negative effects. Little, though, is known about how early childhood education and care (ECEC) practitioners work with children in poverty and the attainment gap between such children and their peers remains significant within England and the US. This article reports research using a mixed methodology which explored these issues in localities across both these countries. We argue a dominant technocratic model of early years provision in these contexts creates normalisation and diversity reduction. This, and austerity measures, stymie pedagogical space and practice organising out listening to children in poverty. We suggest this may help explain why the attainment gap remains so stubbornly resistant to reduction across these countries.